Effect of Compound Chuanxiong Capsule on Inflammatory Reaction and PI3K/Akt/NF-κB Signaling Pathway in Atherosclerosis - Kang, Qunfu (Evid Based Complement Alternat Med, 2015)
Compound Chuanxiong Capsule (CCC), a Chinese herbal compound, can exhibit antiatherosclerotic effect; however, its mechanism is still unclear. This study is designed to study the mechanism of CCC on atherosclerosis in the ApoE-knockout (ApoE(−/−)) mice fed with a high-fat diet. After 6 weeks of high-fat feeding, 40 ApoE(−/−) mice were randomized (n = 10) and treated with lipitor, high-dose or low-dose CCC, or distilled water (ApoE(−/−) group) for 7 weeks. The blood lipids in serum and the plaque areas of the mice were measured and the mRNA expressions of phosphatidylinositol-3-kinases (PI3K), Akt, nuclear factor-kappa B (NF-κB), tumor necrosis factor-α (TNF-α), and interleukin-6 (IL-6) of the aortae were determined. The data showed that CCC can significantly decrease the levels of blood lipids, atherosclerosis index, and plaque areas and increase collagen proportion in plaques as compared with the untreated mice (p < 0.05, p < 0.01). In addition, CCC can significantly reduce the mRNA expressions of PI3K, Akt, NF-κB, IL-6, and TNF-α in the mice fed with a high-fat diet (p < 0.001). Thus, we concluded that CCC can inhibit inflammatory reaction in the ApoE(−/−) mice fed with a high-fat diet. This mechanism may be attributed to regulating PI3K/Akt/NF-κB signaling pathway.